2019
DOI: 10.3389/fimmu.2019.01136
|View full text |Cite
|
Sign up to set email alerts
|

TLR4, but Neither Dectin-1 nor Dectin-2, Participates in the Mollusk Hemocyanin-Induced Proinflammatory Effects in Antigen-Presenting Cells From Mammals

Abstract: Mollusk hemocyanins have biomedical uses as carriers/adjuvants and nonspecific immunostimulants with beneficial clinical outcomes by triggering the production of proinflammatory cytokines in antigen-presenting cells (APCs) and driving immune responses toward type 1 T helper (Th1) polarization. Significant structural features of hemocyanins as a model antigen are their glycosylation patterns. Indeed, hemocyanins have a multivalent nature as highly mannosylated antigens. We have previously shown that hemocyanins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 95 publications
(127 reference statements)
0
30
0
Order By: Relevance
“…Unlikely, KLH is formed by homododecamers, whose stability depends on Ca +2 and Mg +2 for maintenance. 25 Our results showed that TRIMELVax immunizations activate effective cell-mediated and humoral immune responses against B16F10 tumors, inhibiting tumor growth and prolonging mice survival, even in the absence of combined therapy with anti-PD-1 antibodies.…”
Section: Introductionmentioning
confidence: 56%
See 3 more Smart Citations
“…Unlikely, KLH is formed by homododecamers, whose stability depends on Ca +2 and Mg +2 for maintenance. 25 Our results showed that TRIMELVax immunizations activate effective cell-mediated and humoral immune responses against B16F10 tumors, inhibiting tumor growth and prolonging mice survival, even in the absence of combined therapy with anti-PD-1 antibodies.…”
Section: Introductionmentioning
confidence: 56%
“…9 10 In contrast, TRIMEL seems to generate the appropriate combination of DAMPs capable of inducing an effective DC maturation. 8 9 CCH has potent immunostimulatory effects, whose adjuvant properties could be partially explained by its carbohydrate-based high complexity and stability, 24 which activate APCs via the interaction with the C-type lectin and Toll-like receptors (TLRs) such as mannose receptor and TLR4, respectively, 25 strengthening innate and adaptive immune responses in mammals, making them useful in cancer immunotherapy. 26 30 Notably, treatment of B16F10 tumor-bearing mice with TRIMEL/CCH or combined cell lysates in the absence of CCH did not prevent tumor growth ( figure 2B), indicating that every vaccine component is crucial for induction of protective responses in our model.…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, KLH binding to human MR triggers proinflammatory responses in APCs (29). Similarly, TLR4 has been shown to participate in the immunostimulatory effects of CCH, FLH, and KLH in murine APCs (30). All these receptors recognize glycosylated structures from pathogens and promote endocytosis, proinflammatory responses, and antigen presentation to T lymphocytes (3133).…”
Section: Introductionmentioning
confidence: 99%